Engineering the shape of one-dimensional metallic nanostructures via nanopore electrochemistry. (February 2022) - Jeon, Yoo Sang; Park, Bum Chul; Ko, Min Jun; Moon, Jun Hwan; Jeong, Eunjin; Kim, Young Keun
Highlights: Nanopore electrochemistry enables the programmable structural complexity. Chemical atmosphere controls the wire-, tube-, and coil-shaped nanostructures. Vanadyl ions and L-ascorbic acid regulate the flow of electrons. Current intensity determines the reduction area and morphological transformation. Graphical Abstract: ga1 We suggest a facile strategy for regulating nanostructures by selecting the additives during spatially confined template-assisted electrodeposition. The chemical atmosphere fostered between the electrolyte and dielectric surface and the electronic pathway cause different crystallization of the inorganic materials depending on the applied external electric field, which controls the final morphologies. Abstract: The architecture of nanostructures is pivotal to determine material properties at the nanoscale, indicating the importance of harnessing sophisticated nanochemistry to elicit desirable material morphology with uniformity. The simplicity of template-assisted electrodeposition makes it a promising strategy for the fabrication of anisotropic nanomaterials. However, a challenge it faces is the complexity of the materials. This study presents a facile strategy and fabrication mechanism to synthesize nanotubes or nanocoils by selecting additives such as vanadyl ions and L-ascorbic acid. Vanadyl ions stick to the protonated anodized aluminum oxide surface, paving the way for electronic conduction. When a higher electrical field is applied, linear sweep voltammetry implies surface conduction mode is dominant in the spatially confined template. As L-ascorbic acid is included in the electrolyte, the nanostructure can be regulated from nanotubes to nanocoils. The nanocoils consist of numerous nanocrystalline primary particle considered as building blocks, and their relationship affects the final structures. The reaction product, vanadyl ascorbate, acts as a hurdle by partially hindering surface conduction and a helical modifier, inducing the formation of primary particle and their nanocoil assembly. Finally, a state diagram is provided to illustrate the diverse nanostructures at optimized applied current and additive ratio conditions.